Carbon-coated hydrogen fuel cell bipolar plate
Patent Information
- Application Number
- CN202311385862.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-11
- Filing Date
- 2021-07-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-07-14
AI Technical Summary
该文件没有公开这种涂覆基板作为双极板的用途
[0031]本发明的双极板的优点可以包括一项或多项或全部:与传统的镀金双极板相比,改性的耐蚀性,减少电极材料的浸出(例如减少离子浸出),成本更低。
Smart Images

Figure BDA0004510953140000012 
Figure BDA0004510953140000021 
Figure BDA0004510953140000151
Abstract
Description
[0001] This application is a divisional application of the invention patent application filed on July 14, 2021, with application number 202110798362.X and invention title "Carbon Coated Hydrogen Fuel Cell Bipolar Plate". Technical Field
[0002] This invention relates to bipolar plates coated with carbon for use in hydrogen fuel cells (particularly PEM fuel cells). Carbon-coated bipolar plates offer excellent corrosion resistance, providing a more economical alternative to existing coated bipolar plates. Background Technology
[0003] Many deposition techniques are used to coat substrates. Vapor deposition is commonly used to form thin film deposits in a variety of applications, including microelectronics and heavy-duty applications.
[0004] An example of a known physical vapor deposition technique is cathodic arc deposition. In this method, an electric arc is used to evaporate material from a cathode target. The resulting evaporated material then condenses on a substrate, forming a thin film coating. Cathodic arc deposition of tetrahedral amorphous carbon, metals, dielectrics, and other such coatings is known in the art and offers the potential for depositing high-quality thin films.
[0005] Amorphous carbon is a free, active form of carbon that does not exist in a crystalline form. Amorphous carbon films exist in various forms, typically distinguished by the hydrogen content and the spatiotemporal distribution of the carbon atoms in the film. 2 :sp 3 The comparison is categorized.
[0006] In literature examples in this field, amorphous carbon films can be classified into 7 categories (see the table below, excerpted from the Fraunhofer Institute for Schichmann). (Index of Carbon Coating Names):
[0007]
[0008]
[0009] Amorphous carbon and tetrahedral amorphous carbon (aC and ta-C) are characterized by the presence of very little or no hydrogen (less than 10% mol, usually less than 5% mol, and typically less than 2% mol).
[0010] Tetrahedral hydrogen-free amorphous carbon (ta-C) is also characterized by its high content of sp. 3 Hybridized carbon atoms (typically more than 80% of carbon atoms are in sp...) 3 state).
[0011] While the term "diamond-like carbon" (DLC) is sometimes used to refer to all forms of amorphous carbon materials, the term used here refers to amorphous carbon materials other than aC / ta-C. A common method for manufacturing DLC is to use hydrocarbons (such as acetylene), thus introducing hydrogen into the film (compared to aC / ta-C films, which are typically made from hydrogen-free, high-purity graphite).
[0012] In other words, the DLC's SP 2 The carbon content is typically greater than 50% and / or the hydrogen content is greater than 20% mol. DLC can be undoped or doped with metals or nonmetals (see table above).
[0013] Tetrahedral amorphous carbon coatings possess high hardness and a low coefficient of friction, making them excellent wear-resistant coatings. Furthermore, ta-C and aC maintain long-term stability in harsh environments (such as acidic or alkaline conditions), thus showing broad development prospects in corrosion protection applications.
[0014] As awareness of the impacts of climate change grows, research into alternative "fossil-free" energy sources, such as hydrogen, is increasing. Hydrogen fuel cells, which generate electricity by electrochemically oxidizing hydrogen to form water, are already under development.
[0015] A proton exchange membrane (PEM) fuel cell is a widely used type of hydrogen fuel cell. It consists of a semi-permeable membrane that allows protons to pass through while acting as a barrier between electrons and reactants such as hydrogen and oxygen. PEM fuel cells offer many advantages, including high energy conversion efficiency, environmental friendliness, and low operating temperature.
[0016] Because each cell in a PEM fuel cell produces a relatively low voltage, multiple PEM cells can be connected in series to increase the output voltage. Adjacent PEM cells are connected by bipolar plates, which conduct current from one PEM cell to the next. Bipolar plates typically also contain channels on their surface along which reactants or coolant can be fed. As a core component of hydrogen fuel cells, bipolar plates have many important functions, including collecting conductive current, supporting the membrane electrode assembly, uniformly delivering and isolating reactant gases, and rapidly cooling the circulating coolant.
[0017] Although bipolar plates are typically made of metal, they can be coated with corrosion-resistant coatings due to their reactivity with acids. Gold is a commonly used coating for metal bipolar plates. However, the gold coating process significantly increases the cost of the bipolar plates.
[0018] XP028655999 discloses an aluminum bipolar plate having a TiN, CrN, C, C / TiN, C / CrN coating and an aC top layer. WO2013 / 124690 discloses a plate made of steel, aluminum or titanium, TiN, CrN, ZrN, TiC or TiCN layers and a non-hydrogenated amorphous carbon layer. XP085490166 discloses a steel bipolar plate coated with a Ti seed layer, a TiCx intermediate layer and an aC layer. WO 01 / 28019 discloses an aluminum bipolar plate coated with a first layer including Ti, a second layer including TiAlN and a hydrophobic graphite outer layer. EP3670696 discloses a steel substrate coated with a seed layer, a barrier layer including DLC deposited by CVD, and a ta-C layer deposited by CVA. This document does not disclose the use of such coated substrates as bipolar plates. CN106 374116 discloses a stainless steel bipolar plate having a high-entropy alloy bottom layer, a high-entropy alloy-carbon mixed transition layer, and an outer amorphous carbon layer. EP3650582 discloses a multilayer coating, which sequentially includes a SiC seed layer, an insulating layer (e.g., AlN, SiSi3N4, Al2O3), an interface layer, and one or more ta-C layers. This document does not disclose the use of such a coating on a bipolar plate. CN 109560290 discloses a bipolar plate (e.g., steel) having a conductive coating (metal oxide, e.g., ITO), a corrosion-resistant coating (e.g., Cr or Ti), and an aC top coating. CN 110783594 discloses a stainless steel bipolar plate coated with a Ni layer, a graphene layer, and an outer amorphous carbon layer.
[0019] Therefore, there is a need for alternative bipolar plates that exhibit good corrosion resistance and are preferably more economical than currently available bipolar plates. Summary of the Invention
[0020] This invention provides electrodes coated with amorphous carbon (aC), particularly bipolar plates, for use in hydrogen fuel cells (especially PEM fuel cells). The electrodes, such as aC-coated bipolar plates, have exhibited low ion leaching and are therefore relatively corrosion-resistant.
[0021] Therefore, the present invention provides an electrode for fuel, in a preferred embodiment being a bipolar plate for a PEM hydrogen fuel cell; the electrode is coated with a carbon-containing coating, wherein the carbon-containing coating comprises aC. Preferably, the coating comprises a layer of aC and typically this layer is the uppermost layer of the coating (i.e., the coating exposed to the atmosphere).
[0022] The coating may further include aC-free layers, which increase the coating’s corrosion resistance and / or improve the adhesion of the aC-containing layers to the underlying substrate.
[0023] Accordingly, the present invention also provides a bipolar plate for a PEM hydrogen fuel cell coated with a carbon-containing coating, wherein the carbon-containing coating comprises, in sequence:
[0024] a) A seed layer containing a metal or metal alloy;
[0025] b) An interface layer comprising carbides or nitrides of the metal or alloy in the seed layer; and
[0026] c) The top layer contains aC.
[0027] The present invention also provides a method for coating a bipolar plate for a PEM hydrogen fuel cell with a carbon-containing coating, the method comprising:
[0028] a) Apply a seed layer containing a metal (e.g., titanium) or alloy to the electrode plate (e.g., by HIPIMS, DC pulse or metal FCVA deposition process);
[0029] b) Applying (e.g., by sputtering) an interface layer comprising a nitride or carbide of the metal or alloy (e.g., titanium nitride) to the seed layer; and
[0030] c) Apply a layer containing aC on the interface layer (e.g., via an FCVA process).
[0031] The advantages of the bipolar plate of the present invention may include one or more or all of the following: modified corrosion resistance, reduced leaching of electrode materials (e.g., reduced ion leaching), and lower cost compared to conventional gold-plated bipolar plates.
[0032] In embodiments of the electrodes, plates, and methods of the present invention, aC is optionally in the tetrahedral form of amorphous carbon, i.e., ta-C. Detailed Implementation
[0033] The present invention preferably provides an electrode with a coating comprising an amorphous carbon layer and other layers deposited as described herein. The present invention provides an electrode with a coating that exhibits suitable hardness and high abrasion resistance in use, and now possesses good corrosion resistance due to one or more intermediate CVD deposited layers. Tests shown below in specific embodiments demonstrate the improved properties of the electrode / plate according to the present invention.
[0034] The electrode can be a bipolar plate; accordingly, the present invention provides a bipolar plate for a PEM hydrogen fuel cell coated with a carbon-containing coating, wherein the carbon-containing coating comprises or is composed of aC.
[0035] Preferably, the coating comprises a layer of aC, which is typically the topmost layer of the coating (i.e., the layer of the coating exposed to the atmosphere). aC can be ta-C.
[0036] The coating may also include one or more additional layers between the substrate and the aC layer to improve the adhesion of the aC layer to the substrate and / or to impart further corrosion resistance to the coating.
[0037] The coating on the electrode (e.g., a bipolar plate) typically includes a seed layer; it is applied to a substrate, which is typically metallic.
[0038] The coating typically also includes an interface layer located between the seed layer and the aC-containing layer (also known as the top or top layer).
[0039] The substrate can also be formed from other materials, such as those commonly used to make bipolar plates. These materials include carbon materials (such as graphite) and composite materials (such as graphite or composite plates). When the substrate is metallic, it can be formed from a single metal or from an alloy (e.g., an alloy of iron, titanium, or aluminum). The metallic substrate is preferably a steel substrate, and more preferably stainless steel, such as SUS304 or 316L stainless steel substrates, which are commonly used to manufacture bipolar plates for PEM batteries. SUS301 and SUS303 stainless steels are also suitable as substrates.
[0040] The size of the metal substrate will, of course, depend on the size of the PEM cell and its intended application. However, the metal substrate (i.e., excluding the coating) typically has a thickness of 0.5 mm or less, such as 0.3 mm or less, preferably 0.2 mm or less (e.g., about 0.05 mm or 0.1 mm); thinner substrates are used, for example, in air-cooled versions of the board.
[0041] Metal substrates typically include channels on their surface, which can be formed by stamping or etching. These channels allow coolant or reagents to transfer between adjacent bipolar plates.
[0042] In a preferred embodiment, a seed layer is deposited on a metal substrate. The seed layer promotes adhesion between the metal substrate and the interface layer, and may also exhibit some corrosion resistance properties. The seed layer comprises (and preferably consists of) a metal or alloy. Preferably, the metal / alloy is selected from chromium, titanium, chromium alloys, and titanium alloys. Even more preferably, the metal in the seed layer is or contains titanium.
[0043] The seed layer typically has a thickness of 0.5 μm or less, suitably 0.4 μm or less, and preferably 0.3 μm or less. Furthermore, the seed layer is typically 0.05 μm or thicker, for example, 0.1 μm or thicker. In the specific example below, the seed layer is approximately 0.3 μm.
[0044] As described above, the seed layer can impart some corrosion resistance to the entire coating; therefore, the deposition of the seed layer should ensure coverage of as much of the substrate as possible. Preferably, the seed layer is deposited at a high density. Therefore, various plasma vapor deposition or chemical vapor deposition techniques can be used to deposit the seed layer. Preferably, the seed layer is deposited by FCVA or multi-arc deposition or sputtering, for example using magnetron sputtering (including high-power pulsed magnetron sputtering, as this improves the density of the coating).
[0045] The seed layer typically contains very few impurities (i.e., the seed layer is usually very pure); for example, the impurity content in the seed layer can be 10% or less, typically 5% or less, preferably 2% or less (e.g., 1% or less). Impurities, as referred to herein, mean any substance other than the material used to constitute the seed layer. For example, if the seed layer is composed of Ti, then any element present in the seed layer other than Ti can be considered an impurity.
[0046] The presence of an interface layer promotes the adhesion of the α-C-containing layer to the seed layer. For the seed layer, the interface layer can also increase the corrosion resistance of the coating. Furthermore, the interface layer can reduce the contact resistance between the electrode and the substrate. Preferably, the interface layer has a relatively low density (compared to the seed layer and the α-C-containing layer) and exhibits pinholes or empty columnar pores within the coating. It can be deposited under conditions that promote low-density coatings and facilitate columnar growth within the coating.
[0047] The interface layer is typically formed of a carbide or nitride of a metal or alloy, and is often formed of a carbide or nitride of the metal / alloy of the seed layer. For example, when the seed layer is a titanium seed layer, the interface layer may comprise titanium carbide, titanium nitride, or a mixture thereof, or consist of the same. Similarly, when the seed layer is a chromium seed layer, the interface layer may comprise chromium carbide, chromium nitride, or a mixture thereof, or consist of the same. Preferably, when the seed layer comprises or is composed of titanium, the interface layer comprises or is composed of titanium nitride.
[0048] The interface layer typically has a thickness of 0.5 μm or less, preferably 0.3 μm or less. Furthermore, the interface layer is typically 0.05 μm or thicker, for example, 0.1 μm or thicker. In the example below, the interface layer thickness is approximately 0.2 μm.
[0049] As mentioned above, the interface layer can impart some corrosion resistance to the entire coating; therefore, the deposition of the interface layer should ensure that it covers as much of the substrate as possible. Thus, various plasma vapor deposition or chemical vapor deposition techniques can be used to deposit the interface layer. Preferably, the interface layer is deposited by sputtering, preferably adjusted to obtain a coating with reduced density.
[0050] The interface layer typically contains very few impurities (i.e., the interface layer is typically very pure); for example, the impurity content in the seed layer can be 10% or less, typically 5% or less, preferably 2% or less (e.g., 1% or less). For example, if the seed layer is composed of titanium nitride, any element present in the seed layer other than Ti or N can be considered an impurity.
[0051] Therefore, the carbon-containing coating may sequentially comprise:
[0052] a) A seed layer containing a metal or alloy;
[0053] b) An interface layer comprising carbides or nitrides of the metal / alloy in the seed layer; and
[0054] c) The top layer contains aC.
[0055] The topmost layer of the coating (i.e., the layer exposed to the atmosphere) is an aC layer. This layer may contain more than 70%, for example more than 80%, preferably more than 90% aC by weight, or the layer may consist entirely of aC. The aC layer is both conductive and corrosion-resistant.
[0056] As stated above, the term "amorphous carbon" (aC) used in this paper refers to sp-containing carbon with low hydrogen content. 2 Amorphous carbon. For example, the hydrogen content of aC may be 10% or less, typically 5% or less, preferably 2% or less (e.g., 1% or less). The hydrogen content percentage provided herein refers to a molar percentage (not a mass percentage of hydrogen).
[0057] Furthermore, it is preferable that aC has a low nitrogen content. For example, aC may have a nitrogen content of 10% or less, typically 5% or less, preferably 2% or less (e.g., 1% or less). The nitrogen content percentage provided herein refers to a molar percentage (not a mass percentage of nitrogen).
[0058] aC's sp 2 The content can be 95% or lower, typically 90% or lower, or 80% or lower, preferably 70% or lower, and most preferably 60% or lower; it can have 20% or more of a specific content. 2 The content is typically 40% or more, or 50% or more. Generally, sp... 2 The carbon content falls between 90% and 40%, suitably between 80% and 50%, preferably between 70% and 40%, and most preferably between 60% and 50% (e.g., sp of aC). 2 (Average content is 55%).
[0059] Additionally, aC's sp 3The content can be 5% or higher, typically 10% or higher, or 20% or higher, preferably 30% or higher, and most preferably 40% or higher; its sp 3 The content can be 80% or less, usually 60% or less, or 50% or less. Typically, sp... 3 The carbon content falls between 10% and 60%, appropriately between 20% and 50%, preferably between 30% and 60%, and most preferably between 40% and 50% (e.g., aC layer sp). 3 The average content can be 45%.
[0060] It is important to note that sp 2 and sp 3 The content of sp can vary throughout the aC layer. The values provided above are intended to represent the sp content in aC. 2 and sp 3 The average content. Therefore, at any specific location within the aC layer, the exact sp content of aC is... 2 and sp 3 The content may differ from the values provided above. However, throughout the entire aC layer, sp 2 and sp 3 The content can fall within the values provided above.
[0061] In this embodiment, the aC layer is a ta-C layer containing ta-C or composed of ta-C. Ta-C is a dense amorphous material, described as being composed of disordered sp... 3 The components are interconnected by strong bonds, similar to those found in disordered diamond (see Neuville S, “New Prospects for Tetrahedral Amorphous Carbon Coatings,” QScience Connect 2014:8).
[0062] (http: / / dx.doi.org / 10.5339 / connect.2014.8). Due to its structure being similar to diamond, ta-C is also a very hard material, with a hardness value typically greater than 30 GPa.
[0063] Ta-C coatings are typically hard and dense. For this invention, exceptionally high hardness may not be necessary. The aC coating / layer provides sufficient hardness while maintaining suitable conductivity. The specific embodiments described below have a coating hardness of approximately 1300 HV and produce good results. An alternative embodiment provides a coating with a hardness of approximately 2000 HV; this coating also produces good results. Generally, while the aC / ta-C deposition process can be adjusted to produce coatings of varying hardness—including extremely high hardness coatings—the coatings of this invention do not need to have excessively high hardness. As mentioned above, relatively low sp3 content is generally associated with lower hardness values. In this case, the substrate of the electrode or bipolar plate may suitably have an aC coating with a hardness of at least 900 HV or at least 1000 HV. The hardness can be in the range of 900 HV-3000 HV, suitably in the range of 1000 HV-2000 HV, preferably in the range of 1500 HV-2000 HV, and most preferably in the range of 1800 HV-2000 HV. Coatings with measured hardness values within these ranges are considered suitable, and for slightly different end applications, sometimes different hardnesses may be appropriate depending on the user's choice.
[0064] Hardness can be properly measured using the Vickers hardness test (developed in 1921 by Robert L. Smith and George E. Sandland of Vickers Ltd.; standard test see ASTM E384-17), which can be used for all metals and has one of the widest testing ranges among various hardness tests. The hardness unit given by this test is called the Vickers taper value (HV), which can be converted to Pascals (GPa). The hardness value is determined by the surface area of the indentation obtained through a load test. For example, martensite is a hard steel with an HV of approximately 1000, while diamond has an HV of approximately 10,000 (approximately 98 GPa). The hardness of diamond can vary depending on the precise crystal structure and orientation, but it is typically between approximately 90 and over 100 GPa.
[0065] The aC may optionally be doped with other materials (metals or nonmetals).
[0066] The aC coating is also preferably free of or substantially free of neutral carbon atoms or particles.
[0067] In contrast, the term "diamond-like carbon" (DLC) used in this paper refers to amorphous carbon other than aC / ta-C. Therefore, DLC has a higher hydrogen content than both, sp 2The carbon content is higher than ta-C. For example, DLC can have 20% or more hydrogen content, typically 25% or more, such as 30% or more. The percentage of hydrogen content provided here also refers to molar percentage (not mass percentage of hydrogen). DLC can have 50% or more sp. 2 Carbon content is typically 60% or higher. Generally, DLCs can have a hydrogen content greater than 20% and a sp2+ content greater than 50%. 2 Carbon content. DLC can be undoped or doped with metals and / or non-metals.
[0068] The thickness of the aC layer is typically 1.0 μm or less, preferably 0.5 μm or less. This layer is typically 0.05 μm or thicker, or more suitably 0.1 μm or thicker, for example 0.2 μm or thicker. In embodiments of the invention, the aC layer thickness is approximately 0.2 μm or approximately 0.3 μm. Preferably, the aC coating of the electrode used in the invention does not contain or consist of DLC and does not fall within the definition of DLC provided herein.
[0069] The density of the aC layer is typically greater than 2.0 g / cm³. 3 For example, greater than 2.5 g / cm³ 3 Or preferably greater than 3.0 g / cm³ 3 For example, 3.5g / cm 3 Or even higher. This high density is due to the extremely small carbon-carbon bonds within the coating (even as low as 1-2 angstroms). With this structure, other atoms, even hydrogen, cannot pass through, thus preventing ion leaching and corrosion.
[0070] aC is typically deposited using cathode vacuum arc deposition techniques, such as filtered cathode vacuum arc (FCVA) deposition. Equipment and methods for FCVA coating are known and can be used as part of the methods described in this invention. FCVA coating equipment typically includes a vacuum chamber, an anode, a cathode assembly for generating plasma from the target, and a power supply for biasing the substrate to a given voltage. The nature of FCVA is conventional and not part of this invention.
[0071] The coated bipolar plates described herein exhibit good corrosion resistance even with relatively thin coating thickness. For example, the overall coating thickness (including the aC-containing layer and, where present, the seed layer and interface layer) is typically less than 2 μm, suitably less than 1.5 μm, and preferably less than 1 μm.
[0072] Many conventional and commercially available deposition techniques are known for depositing layers for the electrodes / plates used in this invention. In the foregoing, some embodiments indicate preferred deposition processes. Generally, the deposition of the layers of this invention can be achieved using processes suitable to a person skilled in the art, including but not limited to one or more known PVD or CVD methods or combinations thereof, including sputtering, magnetron sputtering, high-power pulsed magnetron sputtering, multi-arc ion plating, arc deposition, cathode vacuum arc deposition, filtered vacuum arc deposition, and plasma-enhanced chemical vapor deposition.
[0073] In some embodiments, the interface layer may be adjacent to the top layer containing aC, the interface layer comprising a carbide or nitride of a metal / alloy in the seed layer. Alternatively, the seed layer containing a metal or alloy may be adjacent to the interface layer, the interface layer comprising a carbide or nitride of a metal / alloy in the seed layer. Alternatively, the bipolar plate may be adjacent to the seed layer containing a metal or alloy.
[0074] In some embodiments, the bipolar plate may be adjacent to a seed layer comprising a metal or alloy, and the seed layer comprising a metal or alloy may be adjacent to an interface layer comprising a carbide or nitride of the metal / alloy in the seed layer, and the interface layer comprising a carbide or nitride of the metal / alloy in the seed layer may be adjacent to a top layer comprising aC. For example, after cleaning, the seed layer is directly deposited on the bipolar plate, the interface layer is directly deposited on the seed layer, and the aC layer is directly deposited on the interface layer.
[0075] In a further embodiment, the carbon-containing coating may consist of the following components, in order:
[0076] a) A seed layer containing a metal or alloy;
[0077] b) An interface layer comprising carbides or nitrides of the metal / alloy in the seed layer; and
[0078] c) The top layer contains aC.
[0079] Further embodiments of the present invention are described below:
[0080] The bipolar plate of this invention is coated with a carbon-containing coating, the carbon-containing coating comprising, in sequence:
[0081] a) Titanium seed layer;
[0082] b) Titanium nitride or titanium carbide interface layer; and
[0083] c)aC Top layer.
[0084] The bipolar plate of this invention is coated with a carbon-containing coating, the carbon-containing coating comprising, in sequence:
[0085] a) Chromium seed layer;
[0086] b) Chromium nitride or chromium carbide interface layer; and
[0087] c)aC Top layer.
[0088] The bipolar plate of this invention is coated with a carbon-containing coating, the carbon-containing coating comprising, in sequence:
[0089] a) A seed layer of titanium or chromium alloys.
[0090] b) The nitride or carbide interface layer of the seed layer alloy.
[0091] c)aC Top layer.
[0092] In a specific embodiment, the aC layer has a content greater than 3.0 g / cm³. 3 The density.
[0093] In a further embodiment of the present invention, the bipolar plate is coated with a carbon-containing coating, the carbon-containing coating comprising, in sequence:
[0094] a) Titanium seed layer,
[0095] b) Titanium nitride interface layer
[0096] c) The top layer of aC has a density greater than 3.0 g / cm³. 3 .
[0097] This article also provides a method for coating bipolar plates for PEM hydrogen fuel cells with a carbon-containing coating, the method comprising:
[0098] a) Apply a seed layer containing a metal (e.g., titanium) or alloy to the electrode plate (e.g., by HIPIMS, DC pulse or metal FCVA deposition process);
[0099] b) Applying an interface layer comprising a nitride or carbide (e.g., titanium nitride) of the metal or alloy onto the seed layer (e.g., by sputtering); and
[0100] c) Apply the layer containing aC to the interface layer (e.g., via FCVA process).
[0101] The substrate, seed layer, interface layer, and layer containing aC may have the features, definitions, or limitations described above for the bipolar plate relating to the present invention.
[0102] Example
[0103] The invention will now be described in the following embodiments.
[0104] Example 1 - Preparation of Coated Bipolar Plate
[0105] The coating of 316L stainless steel bipolar plates is as follows.
[0106] Step 1) Sample preparation
[0107] Bipolar plates are cleaned according to the following process:
[0108] a. Use a weak alkaline solution for ultrasonic cleaning to remove oil stains from the surface and runners.
[0109] b. Use an acidic acid solution to remove the oxide layer and any rust on the substrate.
[0110] c. Rinse the substrate with pure water under ultrasonic conditions.
[0111] d. Then the substrate is dried under vacuum for 0.5 hours.
[0112] Step 2) Sample coating
[0113] Coating equipment: FCVA coating machine, which also includes ion etching capability and magnetron sputtering source.
[0114] Process:
[0115] a. Place the cleaned bipolar plate to be coated into the coating chamber, and reduce the pressure inside the coating chamber to 5.0 x 10⁻⁶. -5 Torr (6.6 mPa), heated to 130℃.
[0116] b. Perform ion beam cleaning (using conventional ion beam cleaning methods).
[0117] c. The pressure inside the chamber is further reduced to 2 x 10⁻⁶. -5 (2.6 mPa), and a Ti seed layer was deposited under magnetron sputtering conditions, with a deposition time sufficient to deposit a Ti layer with a thickness of 0.3 μm.
[0118] d. After the seed layer is deposited, the interface layer deposition begins. A TiN interface layer is deposited using a sputtering deposition method with a titanium target in the presence of nitrogen. This deposition step requires sufficient time to deposit a TiN layer with a thickness of 0.2 μm.
[0119] e. After the interface layer deposition is completed, a 0.2 μm aC layer is deposited using filtered cathodic vacuum arc (FCVA) technology. The hardness of aC is approximately 1300 HV. 2 The content was not accurately measured, but it is believed to be in the range of 40-70%.
[0120] f. After deposition is complete, the vacuum chamber is placed at room temperature and pressure, and the coated substrate is removed from the coating chamber.
[0121] The completed coated substrate has the following structure:
[0122] TiN interface layer (0.2μm) Ti seed layer (0.3 μm) Substrate – 316L stainless steel bipolar plate
[0123] Example 2 - Resistance to Ion Leaching
[0124] Ion leaching electrochemical corrosion tests were conducted in a sealed electrochemical corrosion cell using 100 ml of pH 3 H₂SO₄ and 0.1 ppm HF as the electrolyte. The working electrode (WE) used was a coated foil with a 316L stainless steel substrate, free of visible defects. The area of the WE exposed to the electrolyte was approximately 7 cm². 2 The experiment was conducted using a saturated Ag / AgCl as the reference electrode (RE) and a 3cm x 3cm Pt mesh as the counter electrode (CE). An electrochemical potential of 1.6V was applied at 80°C for 10 hours against a standard ordinary hydrogen electrode (NHE), ensuring the experiment was free from contamination by external metal ion concentrations. After testing, the etching solution was stored in a PTFE container and then analyzed by calibrated inductively coupled plasma mass spectrometry (ICP-MS). Fe ion concentrations less than or equal to 50 ppb were acceptable.
[0125] Under the above test conditions, the bipolar plate of Example 1 has an Fe ion concentration of less than 40 ppb.
[0126] We compared the ion leaching of the bipolar plate from Example 1 with that of a commercially available gold-plated bipolar plate. The results were:
[0127] Ion leaching 37ppb 70-80 ppb
[0128] In a direct comparison with industry standard coatings, the coating of Example 1 exhibited better performance.
[0129] Example 3 - Interfacial Contact Resistance (ICR) and Corrosion Current Density
[0130] ICR testing was performed using an electrochemical corrosion cell containing 500 ml of H₂SO₄ at pH 3 and 0.1 ppm of HF as the electrolyte. The working electrode (WE) was a coated 316L foil with no visible defects. The area of the WE exposed in the electrolyte was approximately 1.9 cm². 2 This experiment uses saturated Ag / AgCl as the reference electrode (RE) and a 3cm x 3cm Pt mesh as the counter electrode (CE). After three parallel electrochemical tests, the average value of the ICR measurement at 0.6MPa should meet the requirements of the two final contact resistances in the table below.
[0131] 1.6V 5 hours <![CDATA[≤5mΩcm 2 ]]> 0.84V 96 hours <![CDATA[≤5mΩcm 2 ]]>
[0132] Under the above test conditions, the bipolar plate of Example 1 meets both requirements.
[0133] Furthermore, when tested at a potential of 1.6 Vm, the measured corrosion current density was less than 1 μA / cm. 2 .
[0134] Example 4 - Conductivity
[0135] The conductivity of the bipolar plate obtained according to the present invention was tested using the following methods and schemes:
[0136] The contact resistance between stainless steel and carbon paper was measured using a modified Wang's method.
[0137] All samples (including carbon paper and the tested stainless steel samples) were prepared as wafers.
[0138] The sample diameter is 60 mm, the same as the copper plate in the apparatus. The mating anvil is machined to a flatness of 5-15 μm.
[0139] In these experiments, Toray carbon paper (TGPH-060, non-Teflon-coated) was used as the gas diffusion layer. The thickness of the stainless steel bipolar plate was determined according to the actual design.
[0140] After the stainless steel sample to be tested is coated according to the present invention or prior art, two pieces of carbon paper TGP-H-060 are sandwiched between the carbon paper TGP-H-060, and then two gold-plated copper plates are sandwiched between the carbon paper TGP-H-060.
[0141] Provided by the PSP-2010 programmable power supply: 28.26A (1A / cm) 2 The current was measured at 5 N·s. During the experiment, the compressive force was controlled by the WDW electronic universal testing machine developed by the Changchun Kexin Testing Machine Research Institute. -1 The step size is increased until 60 Ncm is applied to the circular electrode area. -2 A final compression pressure of 0.6 MPa was used to simulate stacking conditions. The total voltage drop was measured using an EDM-3150 multi-display multimeter, and the total resistance could be calculated as follows:
[0142]
[0143] Where R total It is the total resistance, V total It is the total voltage drop set, where I is the current applied to the sample, and A is the current applied to the sample. o It is the surface area (28.26 cm²). 2 ).
[0144] The total resistance is the sum of four interface resistances and three volume resistances: two carbon paper / gold interfaces (R0). c / Au ), the interface between two carbon paper / stainless steel samples (R c / ss Two carbon paper bulk resistances (R) C ) and a stainless steel sample bulk resistance (R SS That is:
[0145] R total =2R C / Au +2R C / ss +2R c +R ss (2)
[0146] Resistance (R) c / Au ) can be represented as:
[0147]
[0148] Where V C / Au It's a voltage drop.
[0149] R c / Au It can also be expressed as:
[0150] R c / Au =2R c / Au +2R c (4)
[0151] Based on equations (2)-(4), the following equations can be obtained:
[0152]
[0153] Where R is the sum of the contact resistance between the carbon paper and the stainless steel sample being tested, and the volume resistance of the carbon paper. Due to the high conductivity of the stainless steel being tested, the volume resistance (R) ss ) is ignored. Therefore, R can be calculated according to equation (5).
[0154] The area resistivity was measured at 12 different locations on the board, and the results were recorded and averaged.
[0155] result
[0156] Gold-plated bipolar plates 1.1um <![CDATA[9mΩ·cm 2 ]]> <![CDATA[8.23x10 -8 A]]> Example 1 0.8um <![CDATA[2mΩ·cm 2 ]]> <![CDATA[1.27x10 -7 A]]>
[0157] These results demonstrate the performance of the coating of the present invention compared to prior art electrodes. The results of Example 1 are improved because the increased contact resistance increases the electrical efficiency loss of the fuel cell and reduces performance.
[0158] It is worth noting that the above gold plating results were all obtained from the following literature when preparing the comparative experiment: Qin Ziwei, Mi Baosen, Chen Zhuo, Wang Hongbin, Research on properties of coating of stainless-steel bipolar plate, Shanghai Metals, 2017, 5, vol 39: 5-10.
[0159] Therefore, the present invention provides electrodes, such as bipolar plates for fuel cells and methods for manufacturing the same.
[0160] Example 5 - Preparation of Coated Bipolar Plate
[0161] Another 316L stainless steel bipolar plate was coated primarily according to the method described in Example 1 above. The substrate bias was modified to increase hardness, which was measured to be approximately 2000 HV, with an average sp2 content of approximately 50%–60% for aC. The layer thickness and composition are as follows:
[0162] TiN interface layer (0.2μm) Ti seed layer (0.3 μm) Substrate - 316L stainless steel bipolar plate.
[0163] This coated bipolar plate exhibits excellent performance, particularly demonstrating ideal low ion leaching and relatively high corrosion resistance.
Claims
1. A bipolar plate for a hydrogen fuel cell, coated with a carbon-containing coating, the carbon-containing coating comprising, in sequence: a) Titanium seed layer; b) Titanium nitride interface layer; and c)aC Top layer, The coating thickness is less than 1.5 μm, the bipolar plate is made of stainless steel, and the density of the aC layer is greater than 2.5 g / cm³. 3 The interface layer has a relatively low density compared to the seed layer and the aC layer; the sp of the aC layer... 2 Carbon content and sp 3 The carbon content varies at any particular location throughout the aC layer, resulting in a relatively low sp. 3 The content is associated with lower hardness values.
2. The bipolar plate according to claim 1, wherein the carbon-containing coating is composed of the following components in sequence: a) Titanium seed layer; b) Titanium nitride interface layer; and c)aC Top layer.
3. The bipolar plate according to claim 1, wherein the aC layer has a molar hydrogen content of 5% or less and / or a molar nitrogen content of 5% or less.
4. The bipolar plate according to claim 1, wherein the aC layer has 50% to 80% sp 2 Carbon content.
5. The bipolar plate according to claim 1, wherein the aC layer has 30% to 60% sp 3 Carbon content.
6. The bipolar plate according to claim 1, wherein the aC layer has a hardness of 1500 HV to 2000 HV.
7. The bipolar plate according to claim 1, wherein the carbon-containing coating comprises, in sequence: a) A titanium seed layer with a thickness of 0.5 μm or less; b) A titanium nitride interface layer with a thickness of 0.5 μm or less; and c) An aC top layer with a thickness of 1.0 μm or less. The bipolar plate is made of stainless steel and has a thickness of 0.5 mm or less.
8. The bipolar plate according to claim 1, wherein the aC layer has a molar hydrogen content of 5% or less and a sp2 content of 50% to 70%. 2 Carbon content and 30% to 60% sp 3 Carbon content.
9. A bipolar plate for a hydrogen fuel cell, coated with a carbon-containing coating, wherein the carbon-containing coating comprises, in sequence: a) A seed layer containing a metal or alloy; b) An interface layer comprising carbides or nitrides of the metal / alloy in the seed layer; and c) The top layer, which contains aC; The density of aC is greater than 3.0 g / cm³. 3 The molar hydrogen content is 5% or less, sp 2 Carbon content is 40% to 70%, sp 3 The carbon content is 30% to 60%; the interface layer has a relatively low density compared to the seed layer and the aC layer, and the sp of the aC layer is... 2 Carbon content and sp 3 The carbon content varies at any particular location throughout the aC layer, resulting in a relatively low sp. 3 The content is associated with lower hardness values.
10. The bipolar plate of claim 9, wherein the aC layer has a molar hydrogen content of 2% or less.
11. The bipolar plate of claim 9, wherein the aC layer has an average sp content of about 55%. 2 Carbon content and / or wherein the aC layer has an average sp content of approximately 45%. 3 Carbon content.
12. The bipolar plate according to claim 9, wherein the bipolar plate is formed of stainless steel.
13. The bipolar plate of claim 9, wherein the bipolar plate is adjacent to the seed layer, the seed layer is adjacent to the interface layer, and the interface layer is adjacent to the top layer comprising the aC layer.
14. The bipolar plate according to claim 9, wherein the carbon-containing coating comprises, in sequence: a) A seed layer with a thickness of 0.5 μm or less, which contains a metal or alloy; b) An interface layer with a thickness of 0.5 μm or less, comprising carbides or nitrides of the metal / alloy in the seed layer; and c) A top layer with a thickness of 1.0 μm or less, which contains aC; The density of aC is greater than 2.0 g / cm³. 3 The molar hydrogen content is 5% or less, sp 2 Carbon content is 40% to 80%, sp 3 The carbon content ranges from 20% to 60%.
15. A hydrogen fuel cell comprising one or more bipolar plates according to claim 1.
16. A method for coating a bipolar plate for a PEM hydrogen fuel cell with a carbon-containing coating, the method comprising: a) Apply a seed layer containing metal to the bipolar plate; b) Apply an interface layer containing the metal as a nitride or carbide to the seed layer; and c) Apply the layer containing aC to the interface layer. The density of aC is greater than 3.0 g / cm³. 3 The molar hydrogen content is 5% or less, sp 2 Carbon content is 40% to 80%, sp 3 The carbon content is 20% to 60%; the interface layer has a relatively low density compared to the seed layer and the aC layer, and the sp of the aC layer is... 2 Carbon content and sp 3 The carbon content varies at any particular location throughout the aC layer, resulting in a relatively low sp. 3 The content is associated with lower hardness values.
17. The method of coating a bipolar plate for a PEM hydrogen fuel cell with a carbon-containing coating according to claim 16, wherein the method comprises: a) Apply a seed layer containing metal to the bipolar plate using HIPIMS, DC pulse, or metal FCVA deposition processes; b) Apply an interface layer containing the metal as a nitride or carbide onto the seed layer by a sputtering process; and c) Apply a layer containing aC to the interface layer using the FCVA process.
18. The method of coating a bipolar plate for a PEM hydrogen fuel cell according to claim 17, wherein the seed layer is titanium and the interface layer is titanium nitride.
Citation Information
Patent Citations
Temperature resistant amorphous carbon coatings
EP3650582A1
Corrosion resistant carbon coatings
EP3670696A1
Corrosion resistant coated fuel cell bipolar plate with filled-in fine scale porosities and method of making the same
WO2001028019A2
Coating with conductive and corrosion resistance characteristics
WO2013124690A1
Coating with conductive and corrosion resistance characteristics
CN104204274A